Technology, applications, and process challenges of dual chamber systems - Werk, Tobias; Hafner, Mathias (Journal of pharmaceutical sciences, 2016)
Dual-chamber systems provide an option as a drug and device combination product, when home care and emergency lyophilized products are intended. Nevertheless, until today, there are only a few products on the market, due to the challenges and limitations in manufacturability, product formulation, and product stability in a dual-chamber configuration, as well as economic considerations. This review serves to describe currently available dual-chamber systems and to discuss factors to be considered for appropriate selection and establishing fill-finish processes.
Gesehen am 23.01.2019